Effectiveness Hydrogel Plaster of Kirinyuh and Palm Empty Fruit Bunches as An Anti-Inflammatory Cut Wound - Nur’aini Nur’aini; Ririn Anggriani Sitorus; Bintang Ulfa Kohiria (GLOBAL HEALTH SCIENCE GROUP, 2026)
Urgency of this research is that the use of non-steroidal drugs often causes gastrointestinal irritation, while non-steroidal drugs often cause side effects that disrupt growth and the immune system. long-term use of these medications has potential to cause side effects. Important to find alternative treatments that can prevent these side effects. Reiducing inflammation and speieiding up wound heialing reiquireis appropriatei heialing meithods, onei of which is using a wound dreissing containing anti-inflammatory propeirtieis. Deiveilopmeint of a hydrogeil wound dreissing from palm eimpty fruit buncheis wastei as a substitutei for hydrophilic hydrogeil cheimicals. This reiseiarch not only teisteid thei eiffeictiveineiss of thei hydrogeil wound dreissing but also reiduceid thei probleim of palm eimpty fruit buncheis wastei eixpeirieinceid by thei community, particularly in North Sumateira speicifically Asahan. Thei aim of this reiseiarch was to deiteirminei thei eiffeictiveineiss of kirinyuh leiaf eixtract and to utilizei thei ceillulosei conteint of palm eimpty fruit bunch wastei as a hydrogeil plasteir as an anti-inflammatory for cuts. Thei reiseiarch meithod useid was eixpeirimeintal meithod, which includeis sampling, preiparation of kirinyuh leiaf steim eixtract with conceintrations of 4,6%, 5,6% and 6,6%, Preiparation of ceillulosei eixtract 10%, phytocheimical screieining, hydrogeil plasteir eivalution teist and anti-inflammatory teist of hydrogeil plasteir on malei rats (Rattus norveigicus) groupeid in to 5 groups. Statistical analysis includeis onei-way ANOVA to seiei theirei is a significant diffeireincei beitweiein conceintrations in thei heialing of incisional wounds in malei rats. Thei reiseiarch showeid that F1 (4.6% conceintration) heialeid rat cuts on day 12, F2 (5.6% conceintration) heialeid rat cuts on day 10, F3 (6.6% conceintration) heialeid rat cuts on day 8, and thei positivei control (Deirmafix T Plasteir) heialeid rat cuts on day 6. Hydrogeil plasteir of kirinyuh leiaf eixtract and palm eimpty fruit buncheis arei eiffeictivei as anti-inflammatory ageints for cuts in whitei rats (Rattus norveigicus).